Code-switching among Stranded Urdu speaking People in Bangladesh: An Observation - Hossain, Md. Amjad (American Journal of Humanities and Social Sciences, 2014)
The use of multiple languages has assumed a considerable importance in the present linguistic world. Monolingual people or countries are hardly found nowadays; even a country though homogeneous, has linguistic minorities who use various languages. People, therefore, tend to develop their ability of speaking several languages simultaneously. Sociolinguistics observes that bilinguals or multilingual often switch from one language to another at the middle of conversation without hampering any motive they are talking for. Different grounds provoke the people to language shifting. In Bangladesh, there are some Urdu speaking people using two languages Bengali and Urdu. The old people who have been living in this country since the then East Pakistan and are habituated to speak Urdu often use Bengali amidst their talks whereas the young people who are used to speaking Bengali, as they are born and brought up in Bangladesh, sometimes do shift languages from Bengali to Urdu. This paper focuses the causes of code switching taking into concern the cases of both the old and the young people shifting their codes either from Urdu to Bengali or from Bengali to Urdu.